Ajustes da variabilidade da frequência cardíaca em repouso e durante o exercício em indivíduos com asma controlada - Araújo, Adriana Sanches Garcia de (2014)
Asthma is a chronic disease, with periods of exacerbation and worsening of airflow obstruction and may be triggered by various stimuli, including exercise, and is associated with dysfunction of the autonomic nervous system (ANS). In this context, two studies were conducted to assess adjustments of ANS in asthmatic volunteers in different situations. The first study was entitled: Increased sympathetic modulation and decreased response of the heart rate variability response in controlled asthma , was designed to evaluate the adjustments of indices of autonomic modulation of heart rate (HR) at rest in supine and seated positions and during the respiratory sinus arrhythmia maneuver (M-RSA). The assessment of 12 asthmatic volunteers included pulmonary function tests and measures of heart rate variability (HRV). The results suggest that in asthma appears to be an association of airflow obstruction with reduced total variability, and in addition, to postural change seems to be reduced adjustment of the sympathetic nervous system in asthmatic women. The second study entitled: Airway responsiveness at exercise recovery and adjustments of heart rate variability at rest and exercise in controlled asthma , evaluated the adjustments of cardiac autonomic modulation during exercise its association with the exercise induced bronchoconstriction. Sixteen asthmatics volunteers underwent constant speed exercise test, forced vital capacity maneuver before and after exercise testing and register of HR and R-R intervals. With this second study, it can conclude that in asthmatics, even with controlled disease, injury presents postural and autonomic adjustments during the year and reduced complexity of dynamical systems of HRV during exercise.